Dietary Patterns and Obesity Risk Among Adults in Mongolia - Dugee, Otgontuya (2007)
Cardiovascular diseases (CVD) and associated nutritional risk factors are among the leading causes of mortality and morbidity in both developed and developing countries. Obesity is an independent risk factor for cardiovascular disease. In Mongolia, cardiovascular diseases have consistently been the leading cause of death since 1995. However, there is a lack of study on the relationship between diet and nutritional risk factors of chronic disease among Mongolians. The purpose of this study was to identify major dietary patterns of the Mongolian adults and to examine the dietary patterns as risk factor of overweight and obesity. Dietary intake is an important determinant of obesity. People consume meals with complex combinations of foods and nutrients. The dietary pattern approach considers the overall diet of persons by taking into account intakes of combined foods and nutrients. This approach is increasingly applied in relations to public health. The cross - sectional study of 420 healthy Mongolian men and women aged 25 years and over was conducted in urban and rural province of Mongolia. This Health and Nutrition survey was carried out jointly by the National Public Health Institute of Mongolia and Kagawa Nutrition University of Japan in 2002 and 2005. Dietary intake was assessed by interview using a semi-quantitative food frequency questionnaire (FFQ) with 68 items. Anthropometric measurements were taken and assessed in accordance with WHO guidelines: weight, height, waist circumference and BMI. Percentage of body fat was measured using a bioelectrical impedance meter. The Principal Component Factor analysis was applied to derive dietary patterns. Twenty one (21) food groups were entered into the factor analysis. Eigenvalue >1.25 criterion and scree plot were used to define the number of factors. Factor scores in all identified factors were calculated for each individual person. Logistic regression analysis was used to calculate odds ratio (OR) and 95% confidence interval (95% CI) for BMI ≥ 25, central obesity and percentage of body fat categories for each quintile of the dietary pattern. An exploratory factor analysis resulted in three types of dietary patterns that accounted for 34.5% of the total variance for the original dietary intake. The Transitional dietary pattern was characterized by higher intake of pork, sausage, cheese, beef, mutton, goat, potato, vegetables and cookies. The Traditional dietary pattern was heavily loaded on milk and milk products, fat and oil, sugar,confectionery and horse meat, whereas the Healthy dietary pattern was high in egg, barley, whole grain bread, vegetable salad, fruits and rice. Male subjects of urban residence, younger age, having higher education, higher income and practice binge drinking tend to be associated with the Transitional dietary pattern. Meanwhile, a higher score for the Traditional pattern was related to subjects with rural residence, intermediary education and physically active. After adjustment for several confounding factors and total energy intake, the Transitional dietary pattern was significantly associated with an increased risk of BMI (odds ratio of the highest quintile vs lowest, 2.47; 95% confidence interval: 1.04–5.86; P for trend <0.002). For the male adults, the Transitional dietary pattern was significantly associated with an increased risk of central obesity and body fat (OR: 4.08; 95% CI: 1.11–14.97; P for trend <0.034 and OR: 4.35; 95% CI: 1.21– 15.58; P for trend <0.024, respectively). As for the Traditional dietary pattern, the higher score was associated with an increased risk of central obesity among the women, after adjustment for confounders (OR: 4.59; 95% CI: 1.58–13.30; P for trend <0.001, and after further adjustment for energy, intake OR: 3.74; 95% CI: 0.92–15.20; P for trend <0.065). On the other hand, the higher score for the Traditional diet was related to a decreased risk of central obesity among the men (Q3vsQ1. OR: 0.26; 95% CI: 0.08–0.79; p<0.018 and Q4vsQ1. OR: 0.29; 95% CI: 0.09–0.95; p<0.041). Meanwhile, the Healthy dietary pattern was significantly associated with a lower risk of BMI (OR: 0.49; 95% CI: 0.25–0.95; P for trend <0.035). In conclusion, this study identified three major dietary patterns and their associations independently with obesity risk among Mongolian adults. Diet,socio-demographic and lifestyle factors should be taken into consideration when designing community-based obesity prevention interventions. The study findings suggest that public health efforts in Mongolia should be targeted at population subgroups in order to address prevailing specific aspects of the Transitional and Traditional dietary patterns, which were found to be associated with increased risk of cardiovascular disease.